Uma análise teórica da evolução da rotação estelar - Maciel, Saulo Carneiro (2007)
In the past 50 years, large eﬀorts have been made toward the understanding of the stellar evolution. In the observational context, large sets of precise measurements of projected rotational velocity were produced, in particular by the Natal and Geneva groups. From these data, it is now possible to establish the behavior of stellar rotation from the turnoﬀ to the red giant branch. In addition, these data have shown the role of tidal eﬀects on stellar rotation in close binary systems. Nevertheless, relatively little attention has been paid to theoretical studies on the evolution of rotation along the HR Diagram, a topic itself directly associated to the evolution of the stars. Basically, there are two reasons for such a fact, (i) spherical symmetry is not assumed, what leads to a substantial increase in the numerical complexity of equations and (ii) non rotating models have been very successful in explaining relevant observational data, including the mass-luminosity relation and chemical abundances. In spite of these facts, it is clear that considerable work remains to be done on the role of rotation in the later stages of the evolution, where clear disagreements arise from confrontations between theoretical predictions and observations. In the present work we study the evolutionary behavior of stellar rotation along the HR Diagram, taking into account constraint conditions issued from recent observational survey of rotational velocity carried out with high precision procedures and new evolutionary codes